ZIJ ULUGH BEK AND HIS INFLUENCE ON ISLAMIC ASTRONOMY DEVELOPMENT IN NUSANTARA - Arwin Juli Rakhmadi; Hariyadi Putraga; Nor Azam bin Mat Noor (Proceeding International Seminar of Islamic Studies, 2023)
Ulugh Bek (d. 853 H/1449 AD) was a Muslim scientist who mastered mathematics and astronomy, he also served as director of the Samarkand Observatory. One of his works in astronomy is “Zij Ulugh Bek” also known as “Zij al-Sulthany”. This zij contains data or astronomical tables of celestial bodies which include studies of hisab and calendar, the celestial bodies' area, planets, and the star's position. In its development, this work significantly influences the Islamic science idea and development in Nusantara, where the Islamic science books written by Islamic science national figures refer to and quote this zij a lot. Genealogically, Ulugh Bek’s Zij is one of the main sources of Islamic science studies development in Nusantara, while the astronomical data contained in this book is fairly accurate so it is still suitable to use at present.